Reasons for Divorce Claims of Female Migrant Workers at the Religious Courts of Ex-Kediri Residency - Anam, Khoirul Anam; Mu'allim, Amir; Yusdani (Universitas Islam Indonesia, 2023)
This research focuses on understanding the reasons behind divorce claims made by female migrant workers at the Religious Courts of ex-Kediri Residency. These female workers have obtained permission from their husbands to seek employment abroad, and their departure is based on mutual agreement between them and their husband. However, while working overseas, these migrant workers file for divorce against their husbands, citing various reasons.This study aims to answer the question of why female migrant workers file for divorce claims at the Religious Courts of ex-Kediri Residency. The research method employed is qualitative research with a socio-legal, conceptual, and philosophical approach. The results of this study indicate six reasons for divorce claims among migrant workers at Religious Court of Kediri Residency. Firstly, economic issues play a significant role. Secondly, domestic violence within the marriage is a contributing factor. Thirdly, third-party interference from family members and friends is prevalent. Fourthly, misappropriation of funds for indulgent and lavish activities occurs. Fifthly, husbands exhibit irresponsibility or abandonment towards their wives. Lastly, some husbands display laziness and solely rely on their wives' monthly allowance. These phenomena call for efforts to restore the humanistic values of Islam, particularly regarding the provision of family livelihood from the perspective of equality and gender justice within migrant workers' families, through the implementation of mubadalah (mutual consultation).